The Ouw Natural Clay Impregnation Using Titanium Dioxide as a Rhodamine B Dyestuff Degrader - Bijang, Catherina M.; Nurdin, M.; Latupeirissa, Jolantje; Aziz, Thamrin; Talapessy, Firda (Indonesian Journal of Chemical Research, 2022)
This study aims to determine the effect of calcination temperature on Titanium dioxide impregnated Ouw Natural Clay (LAO) on the degradation of Rhodamine B dye. The calcination temperature used was 200, 300, and 400 °C. Their radiation was carried out with 3x8 watt UV lamps and sunlight. The degradation percentage of Rhodamine B dye produced by LAO-TiO2 calcined at a temperature of 200, 300, and 400 °C with sunlight were 98.80%, 98.87%, and 96.07%, respectively. The degradation percentage of Rhodamine B dye produced by LAO-TiO2 calcined at temperatures of 200, 300, and 400 °C with the help of UV light were 96.01%, 97.41 %, and 97.18%, respectively.